2006
DOI: 10.1007/s10515-006-5468-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Systematic Analysis of Natural Language Requirements with CIRCE

Abstract: This paper presents CIRCE, an environment for the analysis of natural language requirements. CIRCE is first presented in terms of its architecture, based on a transformational paradigm. Details are then given for the various transformation steps, including (i) a novel technique for parsing natural language requirements, and (ii) an expert system based on modular agents, embodying intensional knowledge about software systems in general. The result of all the transformations is a set of models for the requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 39 publications
0
67
0
1
Order By: Relevance
“…CM-builder [27] managed to extract candidate attributes, entities, and relationships from a 220 word text with 73% recall and 66% precision. CIRCE [3] is a sophisticated tool that generates many different models including ERD, UML, and DFD from NL requirements. Experimental application in three case studies indicated improvements in software model analysis and changing requirements.…”
Section: Nlp For Re: Extracting Models From Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…CM-builder [27] managed to extract candidate attributes, entities, and relationships from a 220 word text with 73% recall and 66% precision. CIRCE [3] is a sophisticated tool that generates many different models including ERD, UML, and DFD from NL requirements. Experimental application in three case studies indicated improvements in software model analysis and changing requirements.…”
Section: Nlp For Re: Extracting Models From Requirementsmentioning
confidence: 99%
“…3 Aside from generating views that highlight a specific role or relationship, it supports filtering based on agile artifacts. In agile software development, user stories are frequently managed in an issue tracker such as Jira.…”
mentioning
confidence: 99%
“…After eliminating duplicates, 361 papers remained to be further investigated. After filtering the results (361 papers) of the electronic search by applying the inclusion/exclusion criteria, we identified 11 papers [6,14,19,21,24,25,36,40,48,51,54] to include. The manual search of journals and conference proceedings yielded an additional six primary studies (i.e., [10,17,18,20,47,49]), and two of them (i.e., [18,49]) are more recent discussions and therefore replaced two of the 11 papers identified from the electronic search (i.e., [19,48]).…”
Section: Statistics From Included Primary Studiesmentioning
confidence: 99%
“…A Glossary describes and classifies all the domain-specific terms used in requirements. A Definition [6] defines the notational short hand for expressing requirements in a succinct, practical, and domain-specific way. A Domain model is created to document the key concepts and the vocabulary of an application domain.…”
Section: Taxonomy Of Requirementsmentioning
confidence: 99%
See 1 more Smart Citation